Complex indicator of quality of sugars and sugar substitutes and their use in the production of confectionery products - Dorohovich, Antonella; Dorohovich, Victoriya; Mazur, Liubov (My University, 2018)
A comprehensive indicator of the quali-ty of sugars and sugar substitutes was calculated according to the principles of quality measurement. The calculation showed the following values of the complex index of sugars’ quality – sucrose, glucose, fructose, maltose, lactose, tagatose, tre-halose: 0.53, 0.46, 0.72, 0.44, 0.26, 0.81, 0.44, 0.47 respectively, and sugar substitutes – sorbitol, xylitol, iso-maltotol, maltitol, erythritol, lactitol: 0.34,0.42, 0.37, 0.47, 0.86, 0. 37 re-spectively.
Keywords: theoretical qualimetry; complex index; Delphi method; differential indicators; кафедра технології хлібопекарських і кондитерських виробів